Efficacy of hydroxychloroquine and omalizumab in a patient with systemic lupus erythematosus, Hashimoto thyroiditis and refractory chronic spontaneous urticaria - Özdemir, Öner; Dikici, Ümmügülsüm; Karaca, Sena Sultan (Alergologia Polska - Polish Journal of Allergology, 2024)
A 15-year-old girl was admitted to an external center 1 month ago with symptoms of generalized pruritus, rash and blistering all over the body, and swelling of the eyes and lips. The patient was started on desloratadine, but there was no improvement in her symptoms. She had been diagnosed with Hashimoto’s thyroiditis 4 years ago in the pediatric endocrinology department; she had been using levothyroxine since then, and her thyroid disease was under control. The dose of antihistamine treatment was increased and montelukast was added. The patient, who had Raynaud’s phenomenon, was diagnosed with systemic lupus erythematosus and hydroxychloroquine was started, but the symptoms of urticaria and angioedema did not decrease. The patient was then started on omalizumab and urticaria was controlled under hydroxychloroquine + omalizumab. In the third month of omalizumab discontinuation, the patient is receiving hydroxychloroquine and levothyroxine treatments and continues to be followed up, being in remission in terms of chronic spontaneous urticaria.